Physicochemical Properties And Enzyme Activity Of Polyphenol Oxidase And Peroxidase From Fresh Pomelo (Citrus Maxima) Juice - Azman, Nur Thaherah Mior (Universiti Sains Malaysia, 2020)
Pomelo (Citrus maxima) is a native of Southeast Asia and has the potential of being commercialized in form of fruit juice. A study of physicochemical properties of fresh pomelo juice was determined its pH, titratable acidity, total soluble solids, total phenolic content, and vitamin C content in order to obtain useful information in food industries. The pomelo juice fulfilled the requirement as stated in the Food Regulation 1985, Regulation 237 with 9.83 ± 0.12 °Brix which represented the sweetness of the fruit. The pH of pomelo juice was recorded to be 6.24 ± 0.01 which considered as less acidic food with low (0.09 ± 0.01%) titratable acidity value. Furthermore, pomelo juice has the potential to be commercialized as thirst quenching fruit juice due to a considerable amount of total phenolic content and vitamin C 90.09 ± 6.74 mg GAE/100 g and 65.59 ± 2.00 mg/100 mL. The peroxidase (POD) was observed to be present and actively higher than polyphenol oxidase (PPO) whereby the activity of enzyme cannot be detected at pH 6.0 and temperature 25 °C with some modifications on the sample volume thus, POD was found to be useful in this study. The activity of POD was found to be optimum at pH 5.5 and pH 6.0 while the optimum temperature was observed at 60 °C and 70 °C. Hence, pomelo juice is suggested to undergo low temperature long time or LTLT in food industries because high thermal treatment can promote the activity of POD in pomelo juice